KETERKAITAN DIKLAT DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI (Studi Pada Dinas Pendidikan dan Kebudayaan Kabupaten Sumbawa) - Susilawati, Yanti; Haryadi, Wahyu (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to examine the effect of training and competency on employee performance at the Education and Culture Agency of Sumbawa District, either partially or simultaneously. The type of this study was associative. The type of data used in this study is quantitative data in the form of scores from respondents' answers to questions given through a questionnaire. The population in this study was all employees at the Sumbawa Regency Education and Culture Service, totaling 50 people. Seeing that the population in this study is relatively small, less than 100 people, this study used a census sampling technique (saturated sample), which is a sampling technique when all members of the population are used as samples. Statistical tests in this research were carried out using the Stata application (Statistics and Data) to assist with data processing. The Stata output will then be studied using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results of this study showed that the training and competency had a positive and significant effect on employee performance at the the Education and Culture Agency of Sumbawa District, either partially and simultaneously. The training and competency had quite a large ability to effect on employee performance variables at the Education and Culture Agency of Sumbawa District, namely 40%, while the remaining 60% was effected by other variables outside this study model, such as the work motivation, incentives, and organizational culture.